2023
DOI: 10.1128/jmbe.00162-22
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Science Art Exhibit on Public Interest and Student Comprehension of Disease Ecology Research

Abstract: Art is a common approach for communicating and educating about science, yet it remains unclear the extent to which science art can benefit varied audiences in varied contexts. To examine this gap, we developed an art exhibit based on the findings of two publications in disease ecology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Finally, it is worth noting that this assignment can be adapted to almost any STEM topic, from COVID-19 to climate change. Indeed, Ricci et al showed that art exhibits can be used to convey information about disease ecology to broad audiences ( 13 ). Regardless of the topic, this assignment can be utilized by instructors to help students explore scientific concepts in a new and different way.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is worth noting that this assignment can be adapted to almost any STEM topic, from COVID-19 to climate change. Indeed, Ricci et al showed that art exhibits can be used to convey information about disease ecology to broad audiences ( 13 ). Regardless of the topic, this assignment can be utilized by instructors to help students explore scientific concepts in a new and different way.…”
Section: Discussionmentioning
confidence: 99%
“…We cannot forget that science is at the heart of science literacy, and part of science literacy is knowing basic science. In line with current scientific challenges related to public health, Ricci et al ( 3 ) and Mixter et al ( 4 ) provide ideas for teaching and learning about infectious disease, through art (as described here by Ricci et al) and through system-level change and collaboration among novice and experienced educators, professional societies, and policymakers (as described here by Mixter et al). Access to microbiology is also expanded, with Newman et al presenting here a novel card-sorting task involving visual literacy skills ( 5 ) and Joyner and Parks outlining how to develop a public data presentation and an epidemiological model based on current events ( 6 ).…”
Section: Editorialmentioning
confidence: 97%
“…Science literacy skills are required for everyday decision-making and are often applied by nonscientists. These nontechnical audiences are able to understand scientific evidence using primary literature ( 18 ) and develop interest in science using art ( 3 ). Attitudes toward science and trust in scientists became especially important during the COVID-19 pandemic.…”
Section: Editorialmentioning
confidence: 99%
See 1 more Smart Citation
“…A. Russell, 2003). For instance, research has shown that the impact of a science art exhibition on visitors’ interest is stronger among those lacking a career or educational background in science (Ricci et al, 2023).…”
Section: Art Exposure and Interestmentioning
confidence: 99%